Boca de Mono T'dad, B.W.I. - (:unkn) unknown (Pereira and Co., Ltd., 2009)
A picture of the Boca de Mono. In this view you can see two islets and vegetation. Also there is a boat docked near one of the islets.
Colour; Black and White; Style: Landscape; Other: Bordered
Keywords: Trinidad and Tobago; Postcards; Ocean--Trinidad and Tobago; Islands--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Trees--Trinidad and Tobago; Coconut palm--Trinidad and Tobago